2008
DOI: 10.3758/mc.36.6.1057
|View full text |Cite
|
Sign up to set email alerts
|

Putting the psychology back into psychological models: Mechanistic versus rational approaches

Abstract: Two basic approaches to explaining the nature of the mind are the rational and the mechanistic approaches. Rational analyses attempt to characterize the environment and the behavioral outcomes that humans seek to optimize. The rational approach holds that people are adaptive and learn (at the individual or species level) to b behave optimally given the nature of the environment (i.e., given available information or statistics). The formal p product of a rational analysis is an abstract mathematical model (ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…Stewart and Chater (2002; Experiment 1) observed higher classification of an NN-halfway test instance into the more variable category if participants were told, during training, that one of the two categories was more variable. Finally, Sakamoto et al (2008) found that a random presentation of the same stimuli in a category, made the category look more variable and so favored it regarding the classification of an NN-halfway critical instance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stewart and Chater (2002; Experiment 1) observed higher classification of an NN-halfway test instance into the more variable category if participants were told, during training, that one of the two categories was more variable. Finally, Sakamoto et al (2008) found that a random presentation of the same stimuli in a category, made the category look more variable and so favored it regarding the classification of an NN-halfway critical instance.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding its other details, this experiment examined a P-halfway critical instance, rather than the nearest exemplars (Cohen et al, 2001;Stewart & Chater, 2002, Experiment 1;Sakamoto et al, 2008). Also, the category boundaries for the low and high variability categories, regardless of how the test instance was classified, were always 18 simple linear ones (contrast with Cohen et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational-level models that ignore the process can struggle with making fine-grained predictions (Sakamoto et al, 2008) and algorithmic-level mod-2 els that ignore the computational level risk making incorrect or no predictions for task variants (Griffiths & Tenenbaum, 2009;Sanborn et al, 2013). A classic way to combine computational-and algorithmic-level insights is to begin with an algorithmic-level model developed to fit human behavior and then investigate its computational-level properties (Ashby & Alfonso-Reese, 1995;Gigerenzer & Todd, 1999).…”
Section: Preprint Submitted To Elseviermentioning
confidence: 99%